Creep and Yield Model of Ice under Combined Stress - Fish, Anatoly M. (1991)
Constitutive equations and strength criteria have been developed for ice in a multiaxial stress state. The equations developed describe the entire creep process, including primary, secondary, and tertiary creep, at both constant stresses and constant strain rates in terms of normalized (dimensionless) time. Secondary creep is considered an inflection point defining the time to failure (tm). The minimum strain rate at failure is described by a modified Norton-Glen power equation, which, as well as the time to failure, includes a parabolic yield criterion. The yield criterion is selected either in the form of an extended von Mises-Drucker-Prager or an extended Mohr-Coulomb rupture model. The criteria take into account that at a certain magnitude of mean normal stresses the shear strength of ice reaches a maximum value due to local melting of ice. The model has been verified using test data on the yield of polycrystalline ice at -1 1.8 degC and on creep of saline ice at -5 degC, both under triaxial compression. Creep Ice Strength Failure Model Yield